2014
DOI: 10.1111/anae.12746
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the i‐gel® vs laryngeal mask airway in children

Abstract: SummaryWe systematically reviewed randomised controlled trials of the i-gel â vs different types of laryngeal mask airway in children. We included nine studies. There was no evidence for differences in: rate of insertion at first attempt; insertion time; ease of insertion; or gastric tube insertion. The mean (95% CI) oropharyngeal leak pressure was 3.29 (2.25-4.34) cmH 2 O higher with the i-gel, p < 0.00001. The relative rate (95% CI) of a good fibreoptic view through the i-gel was 1.10 (1.01-1.19), p = 0.02. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 87%
“…The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance. The 10-min airway leak pressures are similar to the airway leak pressures demonstrated in recent reports on the LMA ProSeal [2,17,18] and igel [1,15,16] in children.…”
Section: Discussionsupporting
confidence: 85%
“…10,12,25,26 The leak pressures of the i-gel appear to be lower than what has been reported in systematic reviews and meta-analyses in children. 14,15 It is possible that operator inexperience may have contributed to the lower airway leak pressures associated with the i-gel.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] The i-gel TM (Intersurgical; Wokingham, UK) is a newer SGA that has been shown to be effective for primary anesthetic maintenance, exhibiting higher airway leak pressures compared with other commonly utilized SGAs in children. 14,15 Additionally, some studies have also found similarly favourable fibreoptic views of the larynx through the igel when compared with other SGAs, 16,17 making it potentially useful for facilitating tracheal intubations. To date, there is a lack of formal studies assessing the i-gel's suitability as a conduit for FOB-guided tracheal intubation in children.…”
Section: Résumémentioning
confidence: 97%
“…In a recent metaanalysis, a notable advantage of the i-gel was its higher airway leak pressures and better fiberoptic views compared with other SGAs in children. 23 Overall, the i-gel has been shown to be an effective SGA for a variety of children including infants. 24,25 Laryngeal Tube…”
Section: I-gelmentioning
confidence: 99%